EVALUATING SUBSTRATE TYPES FOR ENHANCED HYDROPONIC STRAWBERRY YIELD AND QUALITY (Scientific journal of the Fergana State University, 2025)
Strawberries are a widely consumed fruit, valued for their nutritional benefits and sensory qualities, including high levels of bioactive compounds. Traditional soil-based cultivation poses challenges such as limited growing seasons and susceptibility to soil-borne diseases, prompting interest in hydroponic systems for strawberry production. The choice of substrate plays a critical role in hydroponic systems, influencing water retention, aeration, and nutrient availability, which directly impacts plant growth and fruit quality. This study evaluates three substrates coconut coir, perlite, and soil on their effectiveness in enhancing hydroponic strawberry yield and quality. The experiment, conducted in a controlled hydroponic environment, measured growth parameters including stem height, number of leaves, number of flowers, and flowering rate. Results showed that coconut coir outperformed both perlite and soil, with the highest values across all growth parameters. These findings suggest that coconut coir is the most effective substrate for optimizing hydroponic strawberry growth, making it a suitable choice for hydroponic strawberry production systems aiming to maximize yield and fruit quality.